1979
DOI: 10.1210/jcem-48-5-848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adrenal Suppression with Dexamethasone in Essential Hypertension*

Abstract: The 24-h integrated plasma concentration of aldosterone (IC-ALDO), PRA (IC-PRA), and cortisol (IC-F) were measured in 34 male patients with uncomplicated mild essential hypertension and 15 matched normal controls using a portable 24-h continuous nonthrombogenic blood withdrawal system. The hypertensive were subsequently given 0.5 mg dexamethasone three times per day, resulting in suppression of their urinary excretion of 17-hydroxycorticosteroids and free cortisol. The diastolic blood pressure of the hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…47 It is also relevant that very early studies reported that a proportion of patients with essential hypertension showed a good blood pressure response to low-dose dexamethasone treatment, perhaps consistent with the notion that ACTH was sustaining production of a hypertensinogenic adrenal steroid. 48 Although the precise mechanism of this was never established, it is of interest to speculate that subjects who responded in this way had the defect in 11␤-hydroxylation that we describe. Interestingly, a similar suggestion that a pituitary-derived peptide might lead to adrenal hyperplasia and aldosterone excess in a subgroup of patients with aldosteronism was made Ͼ10 years ago on the basis of histological and biochemical data.…”
Section: Implications Of Altered 11␤-hydroxylation In Hypertensionmentioning
confidence: 79%
“…47 It is also relevant that very early studies reported that a proportion of patients with essential hypertension showed a good blood pressure response to low-dose dexamethasone treatment, perhaps consistent with the notion that ACTH was sustaining production of a hypertensinogenic adrenal steroid. 48 Although the precise mechanism of this was never established, it is of interest to speculate that subjects who responded in this way had the defect in 11␤-hydroxylation that we describe. Interestingly, a similar suggestion that a pituitary-derived peptide might lead to adrenal hyperplasia and aldosterone excess in a subgroup of patients with aldosteronism was made Ͼ10 years ago on the basis of histological and biochemical data.…”
Section: Implications Of Altered 11␤-hydroxylation In Hypertensionmentioning
confidence: 79%
“…Thus, over a very long period, the genetic change in 11β-hydroxylation efficiency (along with an additional environmental or genetic influence) might result in ACTH-driven adrenal zonal hyperplasia and an alteration (steepening of the dose–response relationship) of the response of aldosterone to Ang II and potassium. It is pertinent that very early studies reported that a proportion of patients with essential hypertension showed a good BP response to low-dose dexamethasone treatment, seemingly supporting the suggestion that ACTH was sustaining production of a hyper-tensinogenic adrenal steroid (64). Furthermore, there are reports of increased levels of dehydroepiandrosterone sulfate (an adrenal androgen driven by ACTH) in patients with hypertension (65).…”
Section: Primary Aldosteronism (Pa)mentioning
confidence: 99%
“…It is found in approximately 80% of patients with Cushing's syndrome [1]. In addition, there is some evidence that cortisol may play a role in the pathogenesis of primary hypertension [3,4]. In addition, there is some evidence that cortisol may play a role in the pathogenesis of primary hypertension [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy normotensive subjects oral cortisol administration results in an increased blood pressure [2]. In addition, there is some evidence that cortisol may play a role in the pathogenesis of primary hypertension [3,4].…”
Section: Introductionmentioning
confidence: 99%